BIMBINGAN PRANIKAH SEBAGAI INSTRUMEN HUKUM UNTUK MEMBENTUK KESIAPAN PASANGAN MUDA DALAM BERKELUARGA - Syeh Sarip Hadaiyatullah; Zainal Efendi Hasibuan; Ahmad Alfian Pardede (I’tiqadiah: Jurnal Hukum dan Ilmu-ilmu Kesyariahan, 2026)
Premarital counseling serves as both a legal instrument and an educational medium to prepare young couples for family life. Within the framework of Law Number 1 of 1974 as amended by Law Number 16 of 2019 on Marriage, marriage is regarded as a sacred bond that requires physical, mental, and spiritual readiness. This study aims to analyze the effectiveness of premarital counseling in shaping the preparedness of young couples from the perspective of family law. The research employs a normative-juridical method with a descriptive-analytical approach through the examination of statutory regulations, legal literature, and documents related to the implementation of premarital counseling programs in Indonesia. The findings indicate that premarital counseling contributes to enhancing young couples’ understanding of rights and obligations, conflict management, and child protection. However, its implementation still encounters challenges in terms of accessibility, curriculum standardization, and public legal awareness. Therefore, premarital counseling needs to be strengthened both regulatory and substantively to function effectively as a legal instrument in fostering harmonious and equitable families.